Neddylation: A Versatile Pathway Takes on Chronic Liver Diseases - Yao, Jiping; Liang, Xue; Liu, Yanning; Zheng, Min (Frontiers in Medicine, 2020)
Neddylation is a ubiquitin-like post-translational modification that conjugates neural precursor cell expressed developmentally downregulated-8 (Nedd8) to specific substrates for regulation of protein activity. In light of current researches, neddylation pathway is aberrant in the pathogenesis of many diseases. In our review, we summarize the versatile roles of neddylation in chronic liver diseases (CLDs). CLDs are one of the leading causes of chronic disease associated deaths worldwide. There are diverse etiologic agents causing CLDs, mainly including hepatitis B virus (HBV) infection, non-alcoholic fatty liver disease (NAFLD), liver fibrosis and hepatocellular carcinoma (HCC). So far, however, there remains a paucity of effective therapeutic approach to CLDs. In this review, we summarized the role of neddylation pathway which runs through the chronic hepatitis B/NAFLD-liver fibrosis-cirrhosis-HCC axis, a canonical pattern in the process of CLD development and progression. The dysregulation of neddylation induces and even exacerbates the occurrence and development of CLD. Correspondingly, inhibiting neddylation via MLN4924, a small molecule compound targeting NEDD8-activating enzyme (NAE), can potently alleviate CLD progression and improve the outcome. On this basis, profiling and characterization of neddylation pathway can provide new insights into the CLD pathology as well as novel therapeutic strategies, independently of the etiology of CLD.